2017
DOI: 10.1002/path.4948
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and transcriptomic heterogeneity of colorectal tumours arising in Lynch syndrome

Abstract: Colorectal cancer (CRC) arising in Lynch syndrome (LS) comprises tumours with constitutional mutations in DNA mismatch repair genes. There is still a lack of whole-genome and transcriptome studies of LS-CRC to address questions about similarities and differences in mutation and gene expression characteristics between LS-CRC and sporadic CRC, about the molecular heterogeneity of LS-CRC, and about specific mechanisms of LS-CRC genesis linked to dysfunctional mismatch repair in LS colonic mucosa and the possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 84 publications
2
71
1
Order By: Relevance
“…Despite some differences, MLH1 -/- mice combine several key features of both syndromes. The recently detected heterogeneity of Lynch-associated cancers, being highly immunogenic or not (25), additionally argues in favor of using these mice as a model for Lynch Syndrome as well. All malignant human CMMR-D cancers are ultra-hypermutated.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some differences, MLH1 -/- mice combine several key features of both syndromes. The recently detected heterogeneity of Lynch-associated cancers, being highly immunogenic or not (25), additionally argues in favor of using these mice as a model for Lynch Syndrome as well. All malignant human CMMR-D cancers are ultra-hypermutated.…”
Section: Discussionmentioning
confidence: 99%
“…Already during the early adenoma stage, the immune microenvironment may direct immune system attacks. 36 In tissues highly infiltrated with immune cells, tumors may develop through an early loss of B2M heterozygosity that allows for survival in a highly immunogenic environment (Figure 3). Subgroup analyses linked B2M loss with low levels of MHC class I related genes supporting previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…CD3, CD4, CD8, and CD19), and this is backed up by strong CD4 + staining demonstrated by immunohistochemistry. Moreover, G1 reference mucosa shows higher expression of genes related to MHC antigen presentation and of chemokine receptor–ligand pairs compared with G1 tumours . These data suggest that G1 tumours undergo transcriptional reprogramming to dysregulate the immune response and hence evade immune destruction.…”
Section: Molecular Heterogeneity Of Lynch Syndrome Tumoursmentioning
confidence: 90%
“…Further new evidence now supports the contention that, in addition to different precursor lesions, distinct molecular and cellular subtypes of LS‐CRC exist. Binder et al utilised CRC resection specimens from LS patients to demonstrate at least two distinct genetic subtypes of LS‐CRC, termed G1 and G2 . DNA sequencing showed that G1 tumours have a different mutation spectrum to G2 tumours, with higher mutation numbers and greater MSI.…”
Section: Molecular Heterogeneity Of Lynch Syndrome Tumoursmentioning
confidence: 99%
See 1 more Smart Citation